2023
DOI: 10.3389/fenvs.2023.1084461
|View full text |Cite
|
Sign up to set email alerts
|

Effect of land use and environmental variables on phytoplankton community structure in high-elevation river, upper Yangtze river, China

Abstract: The Qinghai-Tibet Plateau is an ecologically fragile region. The changes in physicochemical parameters of water quality [PPOWQ] and land use types [LUT] in different regions will affect the phytoplankton community in rivers, thus threatening the ecosystem. Taking the phytoplankton community as an indicator variable, it is of great significance to study the relative influence of symbiotic factors on regulating human activities and river ecological protection. The results showed that the proportions of Bacillari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 116 publications
0
3
0
Order By: Relevance
“…The analysis revealed that fluctuations in the phytoplankton community were significantly influenced by weather conditions. In 2019, reduced rainfall and elevated water temperatures primarily contributed to the prevalence of Microcystis species across the surveyed points, resulting in a decline in diversity, abundance, and evenness indices [78][79][80][81]. When comparing the average fluctuations in the cluster indices between 2019 and 2020, it was observed that 2019 exhibited more pronounced fluctuations, possibly due to higher rainfall in 2020, creating a more stable environment for phytoplankton growth [82,83].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis revealed that fluctuations in the phytoplankton community were significantly influenced by weather conditions. In 2019, reduced rainfall and elevated water temperatures primarily contributed to the prevalence of Microcystis species across the surveyed points, resulting in a decline in diversity, abundance, and evenness indices [78][79][80][81]. When comparing the average fluctuations in the cluster indices between 2019 and 2020, it was observed that 2019 exhibited more pronounced fluctuations, possibly due to higher rainfall in 2020, creating a more stable environment for phytoplankton growth [82,83].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al utilized RDA and stepwise multiple linear regression (SMLR) to analyze the relationship between water quality, land use, and phytoplankton communities at multiple scales. They found that land use significantly impacts water quality and phytoplankton, providing valuable insights for the protection of urban rivers [ 17 ]. Ma et al conducted canonical correspondence analysis (CCA) to examine the relationship between phytoplankton and environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of forests, lakes, rivers, and mountains will rise in the future; 75% are convinced of that. Also, the raw material wood itself is gaining in importance for 93% of those surveyed, as this renewable resource is a natural raw material and thus serves to protect the climate ( 22 24 ).…”
Section: Introductionmentioning
confidence: 99%